(untitled) (International Journal of Built Environment and Sustainability, 2017)
Construction projects play an important role in the advancement of a nation through infrastructure development that leads to economic growth. They are planned carefully to accomplish certain goals. However, not all the projects achieved the goals as per planned. Many factors contribute to the successes and failures, and it becomes an interesting arena for research. The primary objective of this paper is to outline the development trend of project success measurement globally and locally. The research method employed was to make selected reviews on critical success factors’ (CSFs) literature and to compare international standards and progress in incorporating human behavioural aspects of project management to the situation in Malaysia. A somewhat similar pattern can be observed in Malaysia where the studies have departed from the usual criteria of time, cost and quality, to define project success in a more holistic way. However, the domestic industry has failed to respond to the emerging trend globally as there has yet been any widely published research on the importance of human-related factors towards project success. A consolidated framework of CSFs has therefore, been proposed in responding to the findings. This paper fulfils an identified need as there has been a dearth of research on the subject matter locally.